Experimental determination and thermodynamic optimization of the CuCl–ZnCl2, ZnCl2–FeCl3, CuCl–FeCl3, CuCl–CuCl2, FeCl2–FeCl3, FeCl2–CuCl2 and CuCl–PbCl2 phase equilibria. (December 2019) - Viitala, Hanna; Taskinen, Pekka; Lindberg, Daniel
Abstract: In copper flash smelting, flue dust causes corrosion problems in the heat recovery boiler of the gas train due to formation of dust accretions on the boiler walls. Within these, presence of heavy metal chlorides results in formation of molten salt deposits causing rapid corrosion. CuCl–ZnCl2, FeCl3 –ZnCl2 and CuCl–FeCl3 systems were studied experimentally by equilibration-quenching, scanning electron microscopy and energy-dispersive X-ray spectroscopy in order to evaluate melting behaviour of these chlorides, typically present in the corrosive dust deposits. In addition, CuCl–PbCl2, CuCl–CuCl2, FeCl2 –FeCl3 and CuCl2 –FeCl2 phase diagrams were optimized incorporating and evaluating all available phase diagram and thermodynamic data on the systems. The modified quasi-chemical model was used to describe the thermodynamic properties of molten phases and compound energy formalism was used to model the terminal solid solutions. The calculated phase diagrams are presented and compared with experimental observations as well as with all available phase diagram data from existing literature. Highlights: CuCl–ZnCl2 phase diagram is optimized for the first time. FeCl3 –ZnCl2 phase diagram is optimized for the first time. CuCl–FeCl3 phase diagram is optimized for the first time. New phase equilibria data for heavy metal chloride systems is measured. Equilibration-quenching method for measuring chloride phase equilibria is tested.